1985
DOI: 10.1099/00207713-35-3-274
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyribonucleic Acid Hybridizations Among Strains of Streptococcus salivarius and Streptococcus bovis

Abstract: The genetic relationships among 33 streptococci that were identified as Streptococcus salivarius or Streptococcus bovis and were isolated from humans were determined by deoxyribonucleic aciddeoxyribonucleic acid hybridization on membrane filters. The phenotypic characteristics of these bacteria were determined by their action on 20 substrates in a commercially prepared system, as well as by colony morphology and conventional tests. The S . sulivurius strains were biochemically heterogeneous but genetically hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 34 publications
4
27
0
Order By: Relevance
“…The DNA relatedness ranged from 48 to 93 % (DT m <6 uC) between different subgroups. The levels of hybridization of total DNA between S. gallolyticus and S. bovis biotype II.2 are similar to the results of Coykendall & Gustafson (1985), Garvie & Bramley (1979) and Osawa et al (1995). Only a few biochemical characteristics (acidification of arbutin and melibiose) distinguish S. macedonicus from S. waius.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The DNA relatedness ranged from 48 to 93 % (DT m <6 uC) between different subgroups. The levels of hybridization of total DNA between S. gallolyticus and S. bovis biotype II.2 are similar to the results of Coykendall & Gustafson (1985), Garvie & Bramley (1979) and Osawa et al (1995). Only a few biochemical characteristics (acidification of arbutin and melibiose) distinguish S. macedonicus from S. waius.…”
Section: Discussionsupporting
confidence: 64%
“…However, phenotypic heterogeneity was recognized among isolates in terms of carbohydrate fermentation, starch hydrolysis and production of glucan from sucrose. These variations led to the description of 'variant strains' of S. bovis by different authors (Coykendall & Gustafson, 1985;Facklam, 1972;Knight & Shlaes, 1985;Nelms et al, 1995). The species S. alactolyticus, S. suis, S. gallolyticus, S. macedonicus, S. waius and S. infantarius were further described.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of DNA. Bacteria were grown and lysed, and the DNA was isolated as described previously (8). Briefly, the cells were harvested from cultures grown in 1 liter of Todd-Hewitt broth with 1% extra glucose.…”
Section: Bacteriamentioning
confidence: 99%
“…bovis, a nonenterococcal lancefield group D streptococcus, is a transient colonic commensal with fecal carriage rate of 5 -13 % in healthy adults (Potter et al, 1998;Dubrow et al, 1991), and accounts for 11-12% of infective endocarditis (Ballet et al, 1995;Kupferwasser et al, 1998). Traditionally, S. bovis has been classified into three distinct biotypes; I, II/1, and II/2, www.intechopen.com based on phenotypical and genetic characteristics (Coykendall & Gustafson, 1985). Further studies using phylogenetic analysis allowed clear and unambiguous differentiation of human clinical isolates and indicated that all strains of S. bovis I and II/2 be identified as S. gallolyticus (Schlegel et al, 2003).…”
Section: Streptococcus Bovismentioning
confidence: 99%